Rational evaluation of the therapeutic effect and dosimetry of auger electrons for radionuclide therapy in a cell culture model - Shinohara, Ayaka; Hanaoka, Hirofumi; Sakashita, Tetsuya; Sato, Tatsuhiko; Yamaguchi, Aiko; Ishioka, Noriko S.; Tsushima, Yoshito (Annals of nuclear medicine, 2018)
Objective Radionuclide therapy with low-energy auger electron emitters may provide high antitumor efficacy while keeping the toxicity to normal organs low. Here we evaluated the usefulness of an auger electron emitter and compared it with that of a beta emitter for tumor treatment in in vitro models and conducted a dosimetry simulation using radioiodine-labeled metaiodobenzylguanidine (MIBG) as a model compound. Methods We evaluated the cellular uptake of 125 I-MIBG and the therapeutic effects of 125 I- and 131 I-MIBG in 2D and 3D PC-12 cell culture models. We used a Monte Carlo simulation code (PHITS) to calculate the absorbed radiation dose of 125 I or 131 I in computer simulation models for 2D and 3D cell cultures. In the dosimetry calculation for the 3D model, several distribution patterns of radionuclide were applied. Results A higher cumulative dose was observed in the 3D model due to the prolonged retention of MIBG compared to the 2D model. However, 125 I-MIBG showed a greater therapeutic effect in the 2D model compared to the 3D model (respective EC 50 values in the 2D and 3D models: 86.9 and 303.9 MBq/cell), whereas 131 I-MIBG showed the opposite result (respective EC 50 values in the 2D and 3D models: 49.4 and 30.2 MBq/cell). The therapeutic effect of 125 I-MIBG was lower than that of 131 I-MIBG in both models, but the radionuclide-derived difference was smaller in the 2D model. The dosimetry simulation with PHITS revealed the influence of the radiation quality, the crossfire effect, radionuclide distribution, and tumor shape on the absorbed dose. Application of the heterogeneous distribution series dramatically changed the radiation dose distribution of 125 I-MIBG, and mitigated the difference between the estimated and measured therapeutic effects of 125 I-MIBG. Conclusions The therapeutic effect of 125 I-MIBG was comparable to that of 131 I-MIBG in the 2D model, but the efficacy was inferior to that of 131 I-MIBG in the 3D model, since the crossfire effect is negligible and the homogeneous distribution of radionuclides was insufficient. Thus, auger electrons would be suitable for treating small-sized tumors. The design of radiopharmaceuticals with auger electron emitters requires particularly careful consideration of achieving a homogeneous distribution of the compound in the tumor.